2012
DOI: 10.1097/crd.0b013e3182532286
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Disease in South Asians

Abstract: It is well established that South Asians living in the western world have a higher burden of cardiovascular disease than other ethnicities. Additionally, South Asians develop cardiovascular disease at a younger age, have a more aggressive form of coronary artery disease, and a higher overall mortality. This predilection seems to be multifactorial and includes a combination of traditional and emerging risk factors with an absence of ethnic-specific prevention and control measures. Future direction points toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Ethnically, South Asians have a higher vulnerability to CAD. 19 Further, there is robust evidence linking Type D personality with adverse outcomes following CAD independent of several known risk factors such as hypertension and disease severity. 44 Taken together with our findings, we recommend further investigation of the potential etiological contribution of Type D personality in causation of MI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethnically, South Asians have a higher vulnerability to CAD. 19 Further, there is robust evidence linking Type D personality with adverse outcomes following CAD independent of several known risk factors such as hypertension and disease severity. 44 Taken together with our findings, we recommend further investigation of the potential etiological contribution of Type D personality in causation of MI.…”
Section: Discussionmentioning
confidence: 99%
“…15 16 17 However, there have been some conflicting reports too which suggested no association between Type D personality and absolute incident CHD risk among older adults without clinical features of CHD at intake. 18 Given the strength of evidence linking Type D personality to poor outcomes in CHD, the availability of a short and convenient instrument to measure Type D scale (DS-14), and the high prevalence and more aggressive nature of CHD among ethnic South Asians, 19 there seems to be a compelling case to study the prevalence and determinants of Type D among Indians with CHD about which there is little literature so far. This would give vital information about the extent of influence of personality, which may presumably vary across cultures, on CHD in the Indian setting.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, such beliefs may partly explain the low PA participation levels ( 36 ). Additionally, previous work has shown that South Asians' beliefs and attitudes have a significant effect on health outcomes, as health beliefs influence health behavior, such as a lower locus of control being associated with an increased risk of MI occurrence ( 47 – 49 ). To combat this issue, modifying illness perception is important to ensure that these individuals believe they have capacity to improve their cardiovascular health ( 50 ).…”
Section: Culture and Illness Perceptionmentioning
confidence: 99%
“…Accordingly, the aforementioned TDF may be used to identify more specific barriers and facilitators that physicians may face with PA prescription, such that interventions may be designed with the intent of targeting these barriers, making the intervention workshops more efficacious ( 111 , 122 , 123 ). Nonetheless, these workshops should (1) emphasize the importance of the cultural sensitivity in PA prescription for SACs and (2) recognize the sociocultural context of SACs' CVD risk; knowledge of these sociocultural variations may help to facilitate the delivery of PA programs that satisfy the cultural preferences of SACs, and ultimately enhance uptake and utilization ( 83 ), and also improve quality of care ( 49 ).…”
Section: Clinician Knowledge In Physical Activity Prescriptionmentioning
confidence: 99%
“…Coronary artery disease (CAD) has become the second leading cause of death after malignant tumor in China, with the prevalence of 6.46% [1,2]. Left ventricular hypertrophy (LVH), an increase in muscle mass of left ventricle, has been identified as a powerful risk factor for future cardiovascular morbidity and mortality, with the risk of cardiovascular events increasing six-fold to eightfold [3].…”
Section: Introductionmentioning
confidence: 99%